Intelligent container shipping sustainability disclosure via stakeholder sentiment views on social media - Zhou, Yusheng (2022)
Sustainability disclosure has been an integral part of stakeholder management by informing a company's stakeholders of its efforts toward sustainability. The United Nations announced 17 sustainable development goals (SDGs), which the container shipping industry shall seek to achieve. This research aims to examine stakeholders’ perceived importance of SDGs based on their reaction to and sentiment toward container shipping companies’ sustainability disclosure on Twitter and Facebook. This research reveals that in the container shipping industry, ‘clean water and sanitation’, ‘gender equality’, ‘life below water’, ‘sustainable cities and communities’, and ‘decent work and economic growth’ are the most important as perceived by stakeholders. Theoretically, this research proposes a method combining sentiment analysis and grey relational analysis to gain insights on enhancing stakeholder engagement and perception through sustainability disclosure using social media data. Managerially, this research provides guidance to container shipping companies on using social media to engage their stakeholders via sustainability disclosure.